MSME Company Performance Model: The Role of Financial Resources and Entrepreneurial Orientation - MUSTAFA (Outline Journal of Economic Studies, 2024)
In an increasingly competitive business world, the performance of small and medium enterprises (SMEs) is an important indicator of a country's economic sector. This study explores the performance model of SMEs by assessing the crucial role of financial resources and entrepreneurial orientation in influencing two key dimensions of performance: profitability and sales growth. The results show that both financial resources and entrepreneurial orientation have significant and positive impacts on SME profitability and sales growth. This finding underscores the importance of adequate access to capital and innovative entrepreneurial orientation in improving business performance. Interestingly, the interaction between financial resources and entrepreneurial orientation shows a positive effect, but is not statistically significant, indicating that the combined impact of these two factors can be influenced by the specific context of SMEs. This study offers new insights for practitioners and policymakers in designing strategies and policies that support SMEs. By understanding how capital and entrepreneurial orientation contribute to business performance, it is hoped that more effective approaches can be developed to facilitate the growth and sustainability of SMEs in Indonesia.